Application of Jane Jacobs’ Theory in the Analysis of the Borders of Territory Monitoring in Urban Spaces from Citizens’ Points of View in Bandar Abbas - Amirhamzeh Shahbazi; Esmaeil zakerimnabi; Alireza Shahbazi (برنامه ریزی فضایی)
AbstractThis research explored the social and cultural dimensions of monitoring urban spaces with a particular focus on the mental approaches and behavioral patterns of citizens in Bandar Abbas, Iran. Upon utilizing a descriptive and analytical methodology, data were collected through surveys from a diverse population aged 15 years and older, employing a 2-stage random sampling method involving 385 respondents. The findings revealed significant variations in how citizens perceived their monitoring territories influenced by factors, such as literacy, gender, age, and residency history. While Jane Jacobs highlighted the importance of physical presence in promoting urban safety, this study suggested that the desire to monitor public spaces was shaped by a range of social, economic, and psychological factors. The research underscored the complexity of urban surveillance, indicating that effective monitoring extended beyond spatial design to encompass the diverse experiences and backgrounds of citizens. Recommendations included adopting a pathological approach to analyze norm-breaking behaviors and enhance community engagement in urban safety initiatives. Keywords: Urban Spaces, Social Interaction, Monitoring, Behavioral Patterns, Cultural Beliefs, Bandar Abbas, Jane Jacobs, Public Safety, Citizen Engagement, Survey Methodology.IntroductionSocial interaction in urban spaces serves as the foundation of community life and understanding the mechanisms of monitoring within these environments is a key focus of contemporary research. This issue can be examined from at least two perspectives: Physical and Spatial Perspective: This viewpoint emphasizes urban design requirements and the physical characteristics of spaces. Social and Cultural Perspective: This approach considers the mental frameworks, cultural beliefs, and behavioral patterns of citizens.The current research specifically targeted the second perspective, aiming to evaluate monitoring and surveillance in urban spaces through the lens of citizens' cultural beliefs and mental approaches. The study sought to identify and analyze the mental boundaries and functional areas of monitoring that manifested in citizens' behavioral patterns. Furthermore, it aimed to explain the social, economic, and spatial factors that influenced these mental approaches and defined the boundaries and functional territories of urban monitoring. According to Jane Jacobs, when people are actively present in public spaces and engage with one another, security and social order emerge naturally. Vibrant streets come alive and become dynamic and safe through the presence of vendors, residents, and pedestrians. Jacobs argued that the concept of "eyes on the street"—the watchful gaze and presence of people in public spaces—serves as one of the most effective tools for enhancing urban security. Thus, from her perspective, urban safety cannot rely solely on police presence or formal monitoring tools. Instead, the diversity of land use and a high level of pedestrian activity, which facilitate informal natural monitoring, are crucial features for ensuring the safety of neighborhoods. Materials & MethodsThis research employed a practical, descriptive, and analytical methodology for data collection, utilizing a survey method with a custom-designed questionnaire. The target population consisted of citizens of Bandar Abbas aged 15 years and older, who were selected through a 2-stage random sampling technique, resulting in a sample size of 385 respondents. To analyze the research data, non-parametric statistical inference models were utilized. Bandar Abbas, the capital of Hormozgan Province and the largest port city in Iran, has a diverse social, administrative, economic, and national profile. The city exhibits a heterogeneous and multicultural context characterized by both modern influences and traditional customs that have persisted over time. This duality reflects the city's remarkable stability, akin to that of other major port cities worldwide. According to the 2015 census conducted by the Iran’s Statistics Center, Bandar Abbas has a population of approximately 526,000 people, including various ethnic groups, such as the Baloch, native Hormozgani minorities, and many Afghan immigrants. The research revealed a complex and significant blend of citizens' attitudes, beliefs, and behavioral patterns, which defined the boundaries of their surveillance territory. Figure 2 illustrates the schematic location of the city within the province and the country. Research FindingsThe findings of this research provided crucial insights into how citizens of Bandar Abbas perceived and engaged in monitoring urban spaces: Territorial Perception:Urban Spaces: 46% of citizens considered urban spaces far from their neighborhoods as part of their monitoring territory, while 66% viewed spaces close to their neighborhoods in the same light.Influence of Literacy: Among the illiterate population, 70% regarded urban spaces far from their neighborhoods as their territory compared to 90% for nearby areas. In contrast, educated individuals reported figures of approximately 50 and 70%, respectively. Gender Differences:Contrary to expectations, a larger percentage of female respondents (63%) expressed a desire to monitor public spaces compared to 38% of male respondents, highlighting a significant gender-based difference in monitoring behavior. Impact of Age:The analysis revealed that age significantly influenced monitoring preferences. Middle-aged and older citizens tended to prefer monitoring spaces far from their neighborhoods, contrary to the expectation that they would favor closer oversight. The inclination to monitor such spaces decreased after age 40, reaching zero among those over 70. Residency History:Citizens born in small towns within Hormozgan exhibited a strong desire to monitor urban spaces away from their neighborhoods (92%), while only 35% of those from larger cities shared this sentiment. Additionally, respondents with a residence history of 11 to 30 years showed a greater tendency to monitor spaces outside their neighborhoods. Statistical Validation:The findings were validated using Chi-Square and Somers’d statistical inference models, confirming the significance of the relationships between literacy, gender, age, and residency history in shaping monitoring behaviors.These findings underscored the complexity of urban monitoring behaviors, suggesting that they were influenced by a multitude of social, economic, and cultural factors beyond mere spatial design. Discussion of Results & ConclusionThe results indicated that 46% of citizens perceived urban spaces far from their neighborhoods as their monitoring territory, while 66% viewed nearby urban spaces in the same light. Among the illiterate population, 70% considered urban spaces far from their neighborhoods as their territory compared to 90% for those within or adjacent to their neighborhoods. For educated individuals, these figures were approximately 50 and 70%, respectively. This disparity highlighted a significant distinction between the perception of spaces far from neighborhoods and those close to them; notably, respondents with higher literacy levels showed increased interest in monitoring public spaces. The intensity of the desire to monitor varied considerably between distant and nearby public areas with a confirmed significant relationship between literacy and the desire to oversee spaces away from one’s neighborhood. Gender also played a crucial role in monitoring preferences. Contrary to expectations that female respondents would be less inclined to monitor public spaces away from their neighborhoods due to conservative tendencies, a substantial 63% of female respondents expressed a desire to engage in monitoring compared to only 38% of male respondents. These findings were validated using Chi-Square and Somers’d statistical inference models. The analysis further revealed that age significantly influenced citizens' monitoring behaviors. Contrary to initial assumptions, middle-aged and older citizens exhibited a desire to monitor spaces far from their neighborhoods influenced by traditional values. The data showed that after age 40, the inclination to monitor such spaces gradually decreased, dropping to zero among individuals over 70 years old. This trend was confirmed by the statistical analysis. Additionally, the desire to monitor urban spaces away from the Mar neighborhood was 92% among those born in small towns in Hormozgan Province compared to just 35% among those from larger cities. Interestingly, although it was anticipated that longer residency in a neighborhood would correlate with a greater desire to monitor public spaces, the analysis revealed that only respondents with a residence history of 11 to 30 years demonstrated a higher tendency to monitor areas "away from their neighborhood". In conclusion, the findings underscored the complexity of urban monitoring behaviors, highlighting how they were shaped by various social, economic, and cultural factors, rather than by spatial design alone.The summary indicated that, contrary to Jane Jacobs' theory, the desire to monitor urban spaces could not be solely attributed to physical and spatial structures or urban design. Instead, factors, such as citizens' occupations, literacy and education levels, age, place of birth, and residence history, along with the economic and social status of their neighborhoods, played a crucial role in shaping their attitudes toward urban monitoring. These dimensions, in conjunction with the considerations outlined by Jacobs, highlighted the complex nature of urban surveillance, which was influenced by various social, economic, and psychological factors. This research presented an innovative perspective by examining how citizens approached the monitoring and surveillance of urban spaces, as well as the social, economic, physical, and spatial factors that informed their willingness to engage in such activities. Building on Jacobs' assertion that the presence of "eyes on the street" enhanced safety and liveliness in public spaces—such as streets, parks, and squares—this study recommends a typological approach to analyze norm-breaking behaviors and the potential reactions of citizens. Such analysis could provide deeper insights into fostering safer and more vibrant urban environments.